Episodic Visual Distortions and Stroke-Like Symptoms in a 56-Year-Old Man With Intravascular Lymphoma. Issue 2 (June 2020) - Chwalisz, Bart K.; Douglas, Vivian P.; Douglas, Konstantinos A. A.; Martinez-Lage, Maria; Kelly, Hilary R.; Cestari, Dean M.
Abstract : Abstract: A healthy 56-year-old man presented with vision changes and left upper extremity motor and sensory changes. MRI of the brain without contrast was significant for multifocal areas of restricted diffusion in multiple vascular territories. Neuro-Ophthalmic evaluation revealed an inferonasal visual field defect in the left eye, thickened choroid on optical coherence tomography, and bilateral delayed arteriovenous and choroidal filling on fluorescein angiogram. Repeat MRI demonstrated interval enlargement of many of the same foci of abnormal diffusion-weighted imaging signal. Computed tomography of the abdomen and pelvis revealed 3 distinct lobulated retroperitoneal masses that were biopsied and found to be consistent with diffuse large B-cell lymphoma. Brain biopsy specimens showed intravascular lymphocytes, confirming a diagnosis of intravascular lymphoma (IVL). In this diagnostically challenging case, a link was established between the presence of multiple strokes (some of which showed slow evolution over time) and retinochoroidal hypoperfusion, which provided a critical clue to the ultimate diagnosis of IVL.